Management Psychology in Educational Organizations: A Systematic Literature Review of Motivation, Communication, and Well-Being as Determinants of School Effectiveness - Nur Faizah Zulfa; Nur Fika Anjani; Haidar Rafli Rasyad; Mu’alimin Mu’alimin (Penerbit Hellow Pustaka, 2026)
The increasingly complex development of educational organizations demands the integration of managerial approaches and psychological aspects in their management. Management psychology is important because it plays a role in understanding motivation, communication, leadership, and human resource well-being, which have a direct impact on the effectiveness of educational institutions. This article aims to analyze and synthesize research trends in management psychology in the educational context over the past five years and identify the dominant dimensions that contribute to improving organizational performance. The research questions focus on: (1) what are the trends and main focuses of management psychology studies in education; and (2) what dimensions are most dominant in improving the effectiveness of educational organizations. This study uses a systematic literature review approach through the Google Scholar database with the help of the Publish or Perish application using the keywords